Guardians of giants: a bibliometric analysis of mahout-elephant relationships and management takeaways for the Nilgiris - Palanivelan, Jaisridhar; Nagarajan, Hariraj; Fernandaz, Cinthia; S, Jasimudeen; Manivasagam, Senthilkumar; Rajagopal, Shanmugam; P, Raja; Bhojan, Vinothkumar; S, Manivasakan (Frontiers in Animal Science, 2025)
The study presents a systematic bibliometric review of mahout-elephant relations and management with specific applications for the Nilgiris region. Asian elephants face significant survival threats including habitat loss and captivity-based exploitation, with approximately 15,000 individuals in captivity across their range countries. Effective conservation strategies require a deep understanding of captive elephant management and welfare issues. Through a systematic review of 63 peer-reviewed articles from 2014-2024, spanning disciplines including animal welfare science, conservation biology, and veterinary medicine, this study identifies critical trends and knowledge gaps. Bibliometric analysis revealed two distinct research clusters with minimal overlap: elephant welfare/management studies and computational approaches. Thailand, particularly Chiang Mai University, emerged as a key research hub with strong international collaborations. Research output has increased significantly since 2016, with a notable acceleration around 2020. Thematic analysis identified concerning shifts in mahout demographics, with younger, less experienced individuals replacing traditional mahouts, compromising vital knowledge transmission. Tourism significantly impacts elephant welfare, with 82% of surveyed Thai camps chaining elephants for extended periods. Health concerns include tuberculosis, with seroprevalence reaching 36% in some populations. Research gaps include limited studies on long-term training effects, elephant psychology, rewilding outcomes, and technological applications in welfare assessment. This review highlights the need for interdisciplinary approaches targeting both elephant and human welfare, emphasizing collaborative efforts among mahouts, local communities, researchers, and conservation agencies to ensure sustainable Asian elephant conservation. The findings and recommendations provide a framework for evidence-based management strategies at the Theppakadu Elephant Camp in the Nilgiris and other similar facilities.